Value Chain Analysis and Strategy to Increase Value Added of Fried Onion Business in Kendari City (Case Study in KWT Matahari) - Elisia Agni Tangdilintin; Hidrawati, Hidrawati; Rosmawaty, Rosmawaty (International Journal of Technology and Education Research, 2024)
This study aims to: (1) analyze the value chain of KWT Matahari Anawai Village, (2) find out the added value of KWT Matahari fried onion business in Anawai Village, and (3) find out the strategy of increasing added value in KWT Matahari Anawai Village. This study is designed as a case study on the fried onion business, the target of the analysis is the Matahari Women Farmers Group (KWT) who has produced fried onions. The data analysis methods used in this study are value chain analysis, added value, and Analytical Hierachy Process (AHP). The results of this study are (1) the KWT Matahari value chain consists of 2 activities, namely the main activity and the supporting activity. The main activities consist of the purchase of shallot commodities from farmers or local markets and the purchase of other ingredients from shops around the production house, the production of fried onions is usually carried out 3 times a week. The production of fried onions has used modern tools, but there are also those that are still manual, so the processing of fried onions usually lasts for 6 hours in 1 production. The second activity is supporting activities, supporting activities consist of planning new product development and financial recording KWT Matahari still uses manual recording. (2) The added value of fried onion products created from the processing of fried onions for a single production process creates an added value of Rp5,202/kg with an added value ratio of 10%. The profit rate is 60.01%, which means that KWT Matahari's fried onion processing business has positive added value. (3) Analytical Hierarchy Process (AHP) can be found that the criteria and strategies for the development of fried onion business that are the most priority at KWT Matahari are product quality for priority criteria with a weight value (0.4704). As for the alternative strategy, the most priority is the prospector strategy with a weight value (0.3513).